A new approach for prediction of the remaining strength of pipeline with external defects. (December 2021) - Gholami, Hojjat; Shahrooi, Shahram; Shishesaz, Mohamad
Highlights: Re-rounding and failure analysis of gouged pipe with dent are conducted. Extensive FEA simulations are simulated. New prediction formula for the re-rounding ratio of the dented pipe is proposed. New prediction formula for the failure pressure of the defective pipe is proposed. Full-scale burst tests are prepared to verify the reliability of formulas. Abstract: Dent and gouge defects are affected by external load on the outer perimeter of the pipelines. The external defects occur both separately and in combination, reducing the remaining strength of the pipelines. Such defects with plastic strain and metal losses lead to stress concentrations. Plastic deformation depends on the initial deflection, springback, and re-rounding behavior of the pipelines. In this research, the semiempirical technique is applied to assess the springback and re-rounding behavior of a pipeline with external defects under internal pressure and the predicted remaining strength of defected pipelines. For this purpose, elastoplastic multi-linear isotropic hardening FE simulation on high-strength carbon steel was utilized to assess the impacts of several factors, such as strain hardening coefficient, pipeline geometry, and dent and gouge geometry on the re-rounding coefficient and remaining strength of defected pipeline. Finally, new methods are proposed for predicting the re-rounding coefficient and the burst pressure of the pipelines with external defects. Full-scale burst tests are implemented to validate the proposed models. Using the proposed formula, the predicted test results of the high- and low-strength pipes demonstrated a good correlation with experimental tests.